The comprehensive effects of visible light irradiation on silver nanowire transparent electrode. (21st August 2018) - Wang, Jun; Jiu, Jinting; Zhang, Shuye; Sugahara, Tohru; Nagao, Shijo; Suganuma, Katsuaki; He, Peng
Abstract: The silver nanowire (AgNW) transparent electrode is one of the promising components for flexible electronics due to its high electrical and thermal conductivity, optical transparency and flexibility. However, the application of the AgNW electrode with an improved performance is generally limited by its poor long-term stability. As the name suggests, the transparent electrode is usually exposed to visible light in various applications. Unlike other electrode materials, AgNWs show unique and complicated behavior under long-term visible light illumination. In this study, the comprehensive effect of visible light irradiation on the AgNW transparent electrode is initially investigated in detail. Light irradiation induces the migration of silver to enhance the nanowire contacts while also leading to the generation and growth of particles and diameter loss in the nanowire. Light irradiation accelerates the sulfidation and oxidation of the AgNWs as well, resulting in the emergence of degradation products on the nanowire surface. All these effects influence the sheet resistance of the AgNW electrode during light illumination. The light-induced change of sheet resistance also relates to the nanowire concentration due to the sensitivity of the wire–wire contact resistance near the percolation threshold. It is believed that this work will be a valuable reference for the design, processing and application of transparent electrodes used in numerous optoelectronic devices.